2023
DOI: 10.1111/oik.09652
|View full text |Cite
|
Sign up to set email alerts
|

Scaling‐up the biodiversity–ecosystem functioning relationship: the effect of environmental heterogeneity on transgressive overyielding

Abstract: Knowledge of how biodiversity sustains ecosystem function comes predominantly from studies focused on small spatial scales. Thus, we know relatively little about the role of biodiversity at larger scales of space and time where habitats become increasingly heterogeneous. Efforts to upscale the relationship between biodiversity and function have yielded inconclusive results. Given that increasing habitat heterogeneity is a ubiquitous consequence of increasing spatial scale, we asked: as habitat heterogeneity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For example, (Germain et al, 2018) found that invasion growth rates of 30 annual plant species only changed with environmental variation in the presence of interspecific competition. A recent analysis of monoculture data from 26 biodiversity-ecosystem experiments showed that in at least half of them, a single species was highest functioning in monoculture in several different environmental contexts (Gamfeldt et al, 2023). The analysis by Gamfeldt et al (2023) includes experiments spanning a range of ecosystem types (terrestrial, freshwater, marine) and organisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, (Germain et al, 2018) found that invasion growth rates of 30 annual plant species only changed with environmental variation in the presence of interspecific competition. A recent analysis of monoculture data from 26 biodiversity-ecosystem experiments showed that in at least half of them, a single species was highest functioning in monoculture in several different environmental contexts (Gamfeldt et al, 2023). The analysis by Gamfeldt et al (2023) includes experiments spanning a range of ecosystem types (terrestrial, freshwater, marine) and organisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of monoculture data from 26 biodiversity-ecosystem experiments showed that in at least half of them, a single species was highest functioning in monoculture in several different environmental contexts (Gamfeldt et al, 2023). The analysis by Gamfeldt et al (2023) includes experiments spanning a range of ecosystem types (terrestrial, freshwater, marine) and organisms (e.g. algae, plants, fungi, primary consumers).…”
Section: Discussionmentioning
confidence: 99%
“…When local BEF mechanisms vary with environmental context, then different BEF mechanisms (Isbell et al, 2018) and patterns (Gonzalez et al, 2020) can arise at landscape scales. The third reason is to aid in predicting how the occurrence, direction, and magnitude of biodiversity mechanisms vary along biotic and abiotic environmental gradients (Gamfeldt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Species diversity can have substantial impacts on ecological processes such as primary productivity, litter decomposition, and nutrient transformation, as shown by syntheses of experimental results (Boyero et al, 2021; O'Connor et al, 2017; Srivastava et al, 2009). However, these experiments are generally performed at small spatial scales and/or under controlled environmental conditions (Cardinale et al, 2007; Gamfeldt et al, 2023). It is not clear yet how the environmental heterogeneity that characterizes larger spatial scales may affect the relationship between biodiversity and ecosystem function (BEF) (Gonzalez et al, 2020, but see Gamfeldt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Large spatial scales are typically associated with high levels of environmental heterogeneity (Hart et al., 2017). If species respond to that environmental heterogeneity and dominate in different environmental conditions, more species may be required to maintain the rate of any given ecosystem function at large spatial scales (Gamfeldt et al., 2023; Isbell et al., 2018; Loreau et al., 2003).…”
Section: Introductionmentioning
confidence: 99%